A Poisson-Boltzmann approach for a lipid membrane in an electric field - Ziebert, Falko; Lacoste, David (New journal of physics, 2010)
The behavior of a non-conductive quasi-planar lipid membrane in an electrolyte and in a static (dc) electric field is investigated theoretically in the nonlinear (Poisson-Boltzmann) regime. Electrostatic effects due to charges in the membrane lipids and in the double layers lead to corrections to the membrane elastic moduli, which are analyzed here. We show that, especially in the low salt limit, (i) the electrostatic contribution to the membrane's surface tension due to the Debye layers crosses over from a quadratic behavior in the externally applied voltage to a linear voltage regime, and (ii) the contribution to the membrane's bending modulus due to the Debye layers saturates for high voltages. Nevertheless, the membrane undulation instability due to an effectively negative surface tension predicted by the linear Debye-Hückel theory is shown to persist in the nonlinear, high-voltage regime.
Gesehen am 23.09.2022